Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 541181 species occurrences available in GBIF matching the query: { "and" : [ "Country is Colombia", "Geometry POLYGON((-81.82 6.90,-81.82 14.86,-69.08 14.86,-69.08 6.90,-81.82 6.90))", "HasGeospatialIssue is false" ] } The dataset includes 541181 records from 353 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0024393-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences